2023
DOI: 10.1007/s44163-023-00055-7
|View full text |Cite
|
Sign up to set email alerts
|

Does GPT-3 qualify as a co-author of a scientific paper publishable in peer-review journals according to the ICMJE criteria? A case study

Abstract: This paper explores the potential for a system to be a co-author on an academic paper based on the criteria proposed by the International Committee of Medical Journal Editors (ICMJE). We used a third generation generative pretrained transformer (GPT-3) to write a review paper on the topic of its choice: The Effects of Sleep Deprivation on Cognitive Function. The system was asked to fulfill the four main criteria for co-authorship as recommended by ICMJE, which includes contributions to the conception or design… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…making significant contributions from initial conception to final production. [30] This two-dimensional framework uncovers the layers of AI's potential in academic collaborations. It ranges from routine task-oriented applications to AI's burgeoning capacity to foster innovative thought and critical reasoning.…”
Section: Collaboration Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…making significant contributions from initial conception to final production. [30] This two-dimensional framework uncovers the layers of AI's potential in academic collaborations. It ranges from routine task-oriented applications to AI's burgeoning capacity to foster innovative thought and critical reasoning.…”
Section: Collaboration Frameworkmentioning
confidence: 97%
“…Osmanovic-Thunström and Steingrimsson showed that GPT-3 can be considered a co-author in their study, emphasizing GPT-3's potential to contribute to scientific work with minimal human intervention. [30] This work transcends their concept by engaging GPT-4 as an advanced research partner.…”
Section: Related Workmentioning
confidence: 99%
“…In a blinded, randomized, noninferiority controlled study, GPT-4 was found to be equal to humans in writing introductions regarding publishability, readability, and content quality [ 52 ]. An article using GPT-3 to write a review on “effects of sleep deprivation on cognitive function” demonstrated ChatGPT’s adherence to ICMJE co-authorship criteria, including conception, drafting, and accountability [ 53 ]. However, it revealed challenges with accurate referencing.…”
Section: Ai’s Unethical Role In Scholarly Writingmentioning
confidence: 99%